Management and characterization of solid waste at Dom Bosco Balsas High School, in Balsas-MA (Research, Society and Development, 2022)
A widely discussed theme is the degradation of the environment, due to the exacerbated consumption of natural and industrialized resources, consequently a growing sequel leaves concerns regarding the final disposal of solid waste produced by the mass population, linked to the pattern of consumerism. It is within this conception that the present work is presented, approaching the items focused on the analysis process around the waste management in the school environment, the waste characterization and how the teaching-learning around this theme is concentrated in the school where the work will be applied, showing that there is a correlation between the data that will be generated with what can and is learned in the classroom. Aiming to analyze the management and characterization of solid waste at Dom Bosco Balsas School, the present work showed that this process of waste characterization, was performed, on December 22, 2021, using the method of quarteamento proposed by ABNT (2004), performing gravimetric characterizations of municipal solid waste at Dom Bosco Balsas School. In addition, waste quantification was performed by determining the apparent specific weight and by determining the total amount of waste. To determine the apparent specific weight, considering that 1m3 corresponds to 1000 liters, it was estimated that 1m3 corresponded to the volume of 4 garbage bags. A total of 37.852 kg was obtained for the 49 dumpsters that were emptied and collected to obtain the waste, i.e., within the estimated apparent specific weight. As for the values, each student produces 0.130 kg of waste daily at school = 0.130 kg/day, and it was observed that the main types of waste observed were paper/cardboard, organic matter and plastic. Seen this, the work hopes to contribute to school management, aiming to implement information to contingency plans in the scope of solid waste management and management and readjust the teaching about environmental education in its realistic prospect for the formation of students who in the future change the paradigm around waste management, whether at the municipal or state level.